2002
DOI: 10.1093/emboj/21.11.2616
|View full text |Cite
|
Sign up to set email alerts
|

The preprotein conducting channel at the inner envelope membrane of plastids

Abstract: The preprotein translocation at the inner envelope membrane of chloroplasts so far involves ®ve proteins: Tic110, Tic55, Tic40, Tic22 and Tic20. The molecular function of these proteins has not yet been established. Here, we demonstrate that Tic110 constitutes a central part of the preprotein translocation pore. Dependent on the presence of intact Tic110, radiolabelled preprotein speci®cally interacts with isolated inner envelope vesicles as well as with puri®ed, recombinant Tic110 reconstituted into liposomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 38 publications
6
84
0
Order By: Relevance
“…However, Toc75 as well as the Tic complex within the inner plastid membrane are generally not believed to be able to transport bulky proteins (26) and it has been shown that plastid preproteins necessarily have to be transported in an unfolded conformation (32). Whereas the pore diameter of Toc75 measures about 14-26 Å (38) and the translocons of the inner plastid membrane Tic110 and Tic20 are in a similar range with 15-31 Å and 7.8-14.1 Å, respectively (39,40), typical N-glycosylation residues comprising 12 glycans have a size of ∼10 × 10 × 30 Å (41, 42), and hence might be too big for translocation. However, as in primary plastids, there is no need for Toc75 to transport glycoproteins, because the addition of glycans occurs exclusively in the ER and Golgi and stromal glycoproteins necessarily use a vesiclemediated route (20,(22)(23)(24)(25), analyses on that issue are not available so far.…”
Section: Discussionmentioning
confidence: 99%
“…However, Toc75 as well as the Tic complex within the inner plastid membrane are generally not believed to be able to transport bulky proteins (26) and it has been shown that plastid preproteins necessarily have to be transported in an unfolded conformation (32). Whereas the pore diameter of Toc75 measures about 14-26 Å (38) and the translocons of the inner plastid membrane Tic110 and Tic20 are in a similar range with 15-31 Å and 7.8-14.1 Å, respectively (39,40), typical N-glycosylation residues comprising 12 glycans have a size of ∼10 × 10 × 30 Å (41, 42), and hence might be too big for translocation. However, as in primary plastids, there is no need for Toc75 to transport glycoproteins, because the addition of glycans occurs exclusively in the ER and Golgi and stromal glycoproteins necessarily use a vesiclemediated route (20,(22)(23)(24)(25), analyses on that issue are not available so far.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions were based on the observation that a urea-denatured fragment of psTic110 gave rise to ion channels when inserted into proteoliposomes. However, the relevance of the reconstitution data are unclear because native psTic110 does not form similar channels in recon-stituted proteoliposomes, nor are similar channels observed in native chloroplast envelope membranes (23).…”
mentioning
confidence: 98%
“…Recently, this model has been challenged by a third hypothesis. This study proposed that Tic110 is a ␤-barrel membrane protein and functions as the protein-conducting channel of the Tic translocon (23). These conclusions were based on the observation that a urea-denatured fragment of psTic110 gave rise to ion channels when inserted into proteoliposomes.…”
mentioning
confidence: 99%
“…The first model describes Tic110 with six transmembrane helices (herein referred to as TM1 to TM6; Figure 1a, model 1) located throughout the polypeptide. The first two transmembrane helices (TM1 and TM2) function as a signal-anchor sequence to target the protein to the inner membrane (L€ ubeck et al, 1997), and the rest of the polypeptide traverses the inner membrane four more times (TM3 to TM6) to form a Ca 2+ -sensitive and cation-selective channel (Heins et al, 2002;Balsera et al, 2009;Kovacs-Bogdan et al, 2011). Tic110 is therefore proposed to be the major channel for translocation of protein across the inner membrane.…”
Section: Introductionmentioning
confidence: 99%